Delineating stocks of Atlantic cod (Gadus morhua) in the Gulf of St Lawrence and Cabot Strait areas using vertebral number - Swain, D. P.; Frank, K. T.; Maillet, G. (ICES Journal of Marine Science, 2001)
Cod ( Gadus morhua ) from several populations overwinter in the Cabot Strait area at the entrance to the Gulf of St Lawrence. We examined the utility of vertebral number for estimating the stock composition of cod aggregations in this overwintering area. Stock-specific mean vertebral numbers were estimated using samples obtained in the 1994–1997 spring (spawning) and summer (feeding) seasons when the populations were geographically separated. Mean vertebral number was significantly lower in the southern Gulf population than in each other population (northern Gulf, southern Newfoundland, Sydney Bight, eastern Scotian Shelf), but did not differ significantly among the other populations. Stock-specific vertebral counts were stable over the study period and, for three of the five stocks (including the large migratory Gulf of St Lawrence stocks), over several year classes. Stock composition of the overwintering aggregations was estimated using samples obtained from synoptic bottom-trawl surveys of the Cabot Strait area in January of 1996 and 1997. In both years, mean vertebral number was significantly lower along the south flank of the Laurentian Channel in NAFO (Northwest Atlantic Fisheries Organization) Divisions 4T and 4Vn than in areas on the north side of the Channel, suggesting that the south side of the Channel was dominated by southern Gulf cod. Maximum likelihood estimates of stock composition based on vertebral number indicated that cod in overwintering aggregations in the 4T–4Vn area were almost entirely (98%) from the southern Gulf stock while southern Gulf cod were almost entirely absent (<0.1%) from the aggregations on the north side of the Laurentian Channel. Bootstrapping indicated that the precision of these estimates was high. Simulations indicated that their bias was negligible. These results suggest that there is virtually no stock mixing across the Laurentian Channel during the overwintering period despite the aggregation of cod from several populations in this small area each year. We ...